Towards a sustainable set of European Core Health Indicators (ECHI) - Mariken J. Tijhuis; Eveline A. van der Wilk; Sarka Dankova; Angela Fehr; Silvia Ghirini; Mika Gissler; Romana Haneef; Heidi Lyshol; Emanuele Scafato; Stefanie Seeling; Hanna Tolonen; Thomas Ziese; et al. (Journal of Health Monitoring)
Background: The European Core Health Indicators (ECHI) are a set of 88 indicators that provide a compact overview of the extensive field of European public health and healthcare. The ECHI set adds value to European Union health information systems (HIS) for both Member States and EU-associated countries and the European Commission by providing a solid, comparable information base on national public health and healthcare trends and developments. The indicators allow for learning by comparison and the list supports the organisation of national health information systems. As the ECHI set was defined more than ten years ago, it is time to review its current needs and readiness for the future. Methods: In this article, we reflect on the sustainability of the ECHI set and explore directions for improving future use, based on the activities in the Joint Action on Health Information (2018 – 2021). There, we looked into ECHI governance and reviewed the set’s metadata, content and link with other indicator sets in the wider European health information landscape. Conclusions: We conclude that in order to remain relevant and keep up with technical and policy developments, the ECHI set needs maintenance and updates. This cannot be achieved in a non-systematic project-based manner; it requires sustainable funding, governance and formalised activities in a permanent structure. We call on the European Commission, Member States, research networks and individual users of the ECHI to take action in this.